Failure of an I‐gel device after use as a conduit for fibreoptic intubation. Issue 2 (11th July 2016) - Sullivan, Gavin
Summary: A 55 year old ASA physical status 1 male presenting for reversal of hartmann's procedure was intubated fibreoptically via an Igel (Intersurgical) supraglottic airway device. The 15mm connector was found to have fractured at the end of the case, requiring removal of the device and conversion to face mask ventilation. The patient had no adverse outcome and recovered uneventfully.